2019
DOI: 10.1111/sdi.12783
|View full text |Cite
|
Sign up to set email alerts
|

Obesity as a barrier to kidney transplantation: Time to eliminate the body weight bias?

Abstract: There is clear evidence that survival rates following transplantation far exceed those for remaining on dialysis, regardless of body size measured by body mass index (BMI). Studies over the past 15 years also suggest little to no difference in long‐term outcomes, including graft survival and mortality, irrespective of BMI, in contrast to earlier evidence. However, weight bias still exists, as access to kidney transplantation remains inequitable in centers using arbitrary BMI limits. Clinicians faced with the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…Several of the findings suggest that comorbid conditions and clinical factors may affect differential rates of PRLT. Older age, obesity, and diabetes were associated with lower rates of listing for repeat transplantation, consistent with findings associated with access to primary transplantation . These results suggest there are a number of clinical factors, including potential noncodified factors that may render patients nonviable for a repeat transplant procedure .…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Several of the findings suggest that comorbid conditions and clinical factors may affect differential rates of PRLT. Older age, obesity, and diabetes were associated with lower rates of listing for repeat transplantation, consistent with findings associated with access to primary transplantation . These results suggest there are a number of clinical factors, including potential noncodified factors that may render patients nonviable for a repeat transplant procedure .…”
Section: Discussionsupporting
confidence: 73%
“…Older age, obesity, and diabetes were associated with lower rates of listing for repeat transplantation, consistent with findings associated with access to primary transplantation. 11,31,44 These results suggest there are a number of clinical factors, including potential noncodified factors that may render patients nonviable for a repeat transplant procedure. [45][46][47][48] Interestingly, results demonstrated a strong association between longer graft survival and likelihood of PRLT.…”
Section: Discussionmentioning
confidence: 88%
“…The optimal approach to weight management in obese kidney transplant candidates has been debated for many decades [5][6][7][8][9]15,16,[24][25][26]. Multiple observational studies have demonstrated that obesity is associated with lower risk of mortality in dialysis patients [27][28][29][30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…Obesity has increased in prevalence among adults with end-stage kidney disease (ESKD) at a rate that has exceeded that of the general population [1][2][3]. The high prevalence of obesity among patients with ESRD is concerning because many transplant centers in the US continue to have pre-specified body mass index (BMI) criteria for candidates to be deemed eligible for transplantation [4][5][6][7]. Although some guidelines no longer recommend use of BMI cutoffs for transplant eligibility determination [8,9], many transplant centers in the US have not yet adopted these recommendations.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the obesity epidemic, nearly 60% of all kidney transplant recipients are overweight or obese, with male predominance [1]. Kidney transplantation (KT) is the most effective method of ESKD treatment but it is still a debatable whether obese patients are suitable candidates for KT [2][3][4][5][6]. Clinical practice guidelines (CPGs) review current research and formulate recommendations based on available evidence and expert opinion.…”
Section: Introductionmentioning
confidence: 99%